The role of Deixis in Rhetoric Space Modelling (on the Material of H. Clinton’s Speech) (Proceedings of Southern Federal University. Philology, 2019)
Olga G. Melnik (Taganrog, Russian Federation)In the given paper the deictic units in the political speech of H. Clinton were singled out and classified with the help of corpus-based approach. Their functioning on textual level was analyzed in order to find out the way the speaker constructs his rhetorical space with help of deictics. We attempted to demonstrate that the concept of rhetorical space can be defined through the concept of deixis. The linguistic analysis of the deictic reference at the personal, temporal and spatial levels showed the way Р. Clinton constructs her rhetorical space, thereby presenting herself to the public. The results obtained indicate a significant presence of a personal deictic reference with the greatest pragmatic potential, while spatial and temporal deictical references have a moderate representation in the corpus. The results for spatial and temporal deixis demonstrate the predominance of proximal reference over the distal. It can be assumed that proximization is a typical device for politicians. Confirmation of this hypothesis can be proposed as a continuation of the conducted study on a more extensive material. However, within the framework of this article, the dominant proximity and inclusiveness is considered as the discursive technique of H. Clinton, used in constructing a rhetorical space in her oral discourse. We come to the conclusion that the use of deictic expressions in political discourse is strictly deterministic: the speaker uses deictic elements to realize her communicative intentions as one of the ways of influencing the cognitive sphere of the addressee.Key words: deictic reference, rhetorical space, political discourse, corpusbased approach, manipulation strategies.DOI 10.23683/1995-0640-2019-1-108-118